(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this paper is to study the involvement of ERP in higher education from various institutes affiliated to different Universities, to enhance the teaching learning process. An innovative adoption perspective is used to examine the research question, focusing in particular on how an ERP supports universities in their innovations. In addition to reviewing the existing literature, the research methodology included a survey of faculty members from different colleges across different universities. There have been significant efforts made by universities and government agencies to improve the quality of higher education. Due to the many changes occurring in higher education, colleges must reassess their strategic direction. There are many factors to consider here, including the characteristics and patterns of distinct processes, the increasing competitiveness and the constant innovation in the teaching and learning processes. Using automation to simplify a complex offering can reduce manual work in repetitive tasks, which will allow faculty and administration to concentrate on providing students with a better learning experience.ERP can accelerate the growth and success of Higher Education Institutions (HEI) by enabling automation in a significant way. The findings of the study revealed that the use of ERP systems is gaining more appeal and acceptance for use in Higher Education Institutions.